Les apprenants prennent la parole : analyse des procedes de cohesion utilises dans le cadre d’une interview avec des locuteurs natifs - Valetopoulos, Freiderikos (Neofilolog, 2021)
The aim of this paper is to explore the strategies used by B1 learners of French as a Foreign Language to construct their discourse and achieve cohesion during an interview with native speakers. The results of this analysis will highlight the characteristics of the development of oral competences. According to the Common European Framework of Reference for Languages, B1 learners can communicate with some confidence on familiar routine and non-routine matters related to their interests and professional field. In an interview task, learners are able to take some initiatives but are very dependent on the interviewer in the interaction. Learners should also be able to use a prepared questionnaire to carry out a structured interview, with some spontaneous follow up questions. The corpus analysis indicated certain strategies expressing inter-sentential and inter-sequential cohesion, such as use of discourse markers (et, donc) or markers of agreement (d’accord).